Theoretical study of the effect of ports in the formation of city systems - Igor Lugo; Gustavo Martínez-Mekler (Journal of Shipping and Trade (JST), 2022)
This paper explores theoretically the formation of a system of cities in which ports affect the spatial location and the size of cities. We use a complex systems and economic geography approach to generate 2D cellular automata to simulate the formation of the landscape of urban agglomerations based on different configurations of port locations. The dynamics of the model shows the emergence of the classical city-size distributions in which the number of ports and their layout affects the growth rate and location of the city-size values. Our findings showed that the two port-city configuration give rise to cities at a long distance from a small number of ports. The size of the cities shows a positive correlations with their distance to ports. A four port-city configuration showed that if the number of ports increases, lower city-sizes are attained and their population displays a negative correlations with their distance to ports. For a lateral configuration with a significantly increase in the number of ports, mainly homogeneous city-size distributions are favored with a slight long-distance size correlation. Therefore, our theoretical model shows a high internal consistency between the theory and assumptions used for describing reliable scenarios in the relationship of ports and urban systems.
Keywords: 650; Cellular automata; City-size distribution; Ports; System of cities